Measurement of 𝐶⁢𝑃 violation in 𝐵0→ 𝜓(→ℓ+⁢ℓ−)⁢𝐾0 𝑆⁡(→𝜋+⁢𝜋−) decays - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2024)
A measurement of time-dependent 𝐶⁢𝑃 violation in the decays of 𝐵0 and ¯𝐵0 mesons to the final states 𝐽/𝜓⁢(→𝜇+⁢𝜇−)⁢𝐾0𝑆, 𝜓⁡(2⁢𝑆)⁢(→𝜇+⁢𝜇−)⁢𝐾0𝑆 and 𝐽/𝜓⁢( →𝑒+⁢𝑒−)⁢𝐾0𝑆 with 𝐾0𝑆 →𝜋+⁢𝜋− is presented. The data correspond to an integrated luminosity of 6 fb−1 collected at a center-of-mass energy of √𝑠 =13 TeV with the LHCb detector. The 𝐶⁢𝑃-violation parameters are measured to be 𝑆𝜓⁢𝐾0𝑆=0.717±0.013⁢(stat)±0.008⁢(syst) and 𝐶𝜓⁢𝐾0𝑆=0.008±0.012⁢(stat)±0.003⁢(syst). This measurement of 𝑆𝜓⁢𝐾0𝑆 represents the most precise single measurement of the CKM angle 𝛽 to date and is more precise than the current world average. In addition, measurements of the 𝐶⁢𝑃-violation parameters of the individual channels are reported and a combination with the LHCb Run 1 measurements is performed.
Gesehen am 30.06.2025
Veröffentlicht: 8. Januar 2024
*LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1080 weitere Personen]
Im Titel sind die Zahl 0 sowie die Plus- und Minuszeichen hochgestellt, der Buchstabe S ist tiefgestellt